ELEMENTS OF DIGITAL EDUCATION IN THE VIRTUAL SPACE OF THE EDUCATIONAL INSTITUTION (Innovative professional education, 2023)
The use of information and communication technologies in education and the creation of digital learning environments made it possible to break down the barriers that exist in traditional study groups. The new learning paradigm will certainly destroy the traditional model of the "teacher-learner" relationship, and will deprive the teacher of the monopoly on creating content and checking the knowledge acquired by the learner. It is appropriate to emphasize that the learning process itself will be the result of group work, where the knowledge created jointly by everyone is also subject to group evaluation. It is worth noting that one of the main characteristics of a digital learning environment is the creation of a space in which not only the conditions for learning are implemented, but also the acquisition of information, collaboration, communication and data management. Thus, there is an opportunity to create communication networks among users, promote learning, cooperation and create new initiatives.
Keywords: information and communication technologies, virtual environment, SCORM standard, digital space